Penanaman Nilai-Nilai Karakter Islami Di RA Uswatun Hasanah Tahun Pelajaran 2022/2023 - Eva M uliati; M. Arzani; Eliyana Eliyana (Jurnal Pembelajaran dan Pendidikan Dasar, 2024)
This research aims to describe the cultivation of Islamic Character Values ​​in Gangga sub-district. This research was carried out at RA Uswatun Hasanah on all students in the second semester of the 2022/2023 academic year. This research is qualitative research with a phenomenological study approach. The subjects of this research were school principals, educators and students. Data collection was carried out using observation, interviews and documentation methods. The techniques used in analyzing data are data reduction, data display, drawing conclusions, and verification. Triangulation is carried out to explain the validity of data using various sources. The results of this research are: 1) The implementation of instilling Islamic character values ​​carried out at RA Uswatun Hasanah is instilled when welcoming children, before entering class, during the learning process, during breaks, and before going home by instilling Islamic values in children such as the value of faith, the value of worship, and the value of morals which are carried out using learning methods including: the playing method, the storytelling method, the conversation method, the exemplary method, and the habituation method. 2) There are supporting and inhibiting factors in instilling Islamic character values ​​at RA Uswatun Hasanah, namely supporting factors such as competent educators, learning that emphasizes Islamic nuances, and a conducive environment. The two inhibiting factors include students lacking focus and getting bored easily, children's characters are different, children's enthusiasm and emotions are less stable, children are hyperactive, facilities and infrastructure are lacking, family backgrounds are less supportive. 3) There is an impact in instilling Islamic character values ​​at RA Uswatun Hasanah, including religious activities such as children becoming familiar with prayer and fasting, daily prayers, Asmaul Husna, Hadith, so that they have morals like the apostles and friends.